Tepung limbah fillet ikan nila sebagai alternatif subsitusi tepung ikan komersial dalam formulasi pakan bagi pertumbuhan benih ikan Nila (Oreochromis niloticus) - Tatuhe, Familia; Lumenta, Cyska; Kalesaran, Ockstan J. (Universitas Sam Ratulangi, 2022)
The research was held on May 7th – 30th 2021 in the Aquaculture Technology Laboratory at the Faculty of Fisheries and Marine of Sam Ratulangi University with the objectives were to determine tilapia fish fillet waste flour’s substitution impact for the growth of the seed and to determine the impact of the tilapia fish fillet waste flour towards the feed’s efficiency. The research lasted for three consecutive weeks. Fish culture container was plastic container with the height of 50 cm and the width of 30 cm for the total of 18 pieces containers. Each container was flowed by 10 liters of water. Fish used had a size of 3 to 5 cm with a weight of 1 gram for each tilapia and stocked as many as 10 fish in each container. The pellets used was flour pellets of tilapia waste fillet with different compositions. Each container was labeled alphabetically: A (0%), B (10%), C (30%), D (30%), E (40%), and F (50%). Frequency of feeding was 3 times a day (08:00 AM, 12:00 AM and 04:00 PM) with a feeding dose of 10%. Water was changed every 4 days. Growth observation was conducted every week using digital scales 0,1 gram. Experimental contrivance was random contrivance exhaustive. Analysis used analysis of diversity. The observed data included relative growth and feed efficiency values. The result showed treatment E gave a better relative growth response and feed efficiency value than other treatments.